Possible prospects for using modern magnesium preparations for increasing stress resistance during COVID-19 pandemic - Maria V. Sankova; Olesya V. Kytko; Renata D. Meylanova; Yuriy L. Vasil'ev; Michael V. Nelipa (Belgorod National Research University, 2020)
Introduction: The relevance of the issue of increasing stress resistance is due to a significant deterioration in the mental health of the population caused by the special conditions of the disease control and prevention during the COVID-19 pandemic. Recently, the decisive role in the severity of clinico-physiological manifestations of maladjustment to stress is assigned to magnesium ions. The aim of the work was to study the magnesium importance in the body coping mechanisms under stress for the pathogenetic substantiation of the magnesium correction in an unfavorable situation of disease control and prevention during the COVID-19 pandemic. Materials and methods: The theoretical basis of this scientific and analytical review was an analysis of modern Russian and foreign literature data posted on the electronic portals MEDLINE, PubMed-NCBI, Scientific Electronic Library eLIBRARY.RU, Google Academy, and CyberLeninka. Results and discussion: It was shown that the total magnesium level in the body plays the indicator role of the body functional reserves. Acute and chronic stresses significantly increase the magnesium consumption and cause a decrease in its body content. Magnesium deficiency is one of the main pathogenetic mechanisms of reducing stress resistance and adaptive body reserves. Arising during the COVID-19 pandemic, increased nervous and emotional tension, the lack of emotional comfort and balance can lead to the onset or deterioration of magnesium deficiency, which manifests itself in mental burnout and depletion of adaptive capacities. The inability to synthesize magnesium in the body necessitates including foodstuffs high in magnesium in the population diet during this period. The appointment of magnesium preparations is pathogenetically justified with moderate and severe magnesium deficiency. This therapy should take into account the major concomitant diseases, severity of magnesium deficiency, and a patient's age. Conclusion: magnesium correction, carried out during the COVID-19 pandemic, will contribute to increasing stress resistance, preventing mental diseases and improving the population's life quality.